Case of unilateral hypoplasia and atresia of the right uterine horn of a gilt - XYLOURI-FRAGIADAKI (Ε. ΞΥΛΟΥΡΗ-ΦΡΑΓΚΙΑΔΑΚΗ) E.; MENEGATOS (Ι. ΜΕΝΕΓΑΤΟΣ) J.; SABATAKOU (Ο. ΣΑΜΠΑΤΑΚΟΥ) O. (Journal of the Hellenic Veterinary Medical Society, 2017)
A case of unilateral hypoplasia and atresia of the uterus horn was described in 19 months old gilt. After repeated returns and 9, in total, unsuccessful artificial inseminations, during and after the third oestrus, the gilt was slaughtered and the right horn of the uterus was found to be "blind" at the level of its borders with the uterus body. It contained 150ml of fluid and was about half the length of the left horn (110cm vs. 190cm). Diffused and welloutlined cysts were observed in both horns of the uterus. Histological examination revealed in the endometrium, edema with abundant loose cellular stroma that surrounded numerous hypoplastic glands and hyperaemic blood vessels with thick walls. It is suggested that the production of PGF2a by the hypoplastic and "blind" horn of the uterus interrupted the pregnancy in the left horn.